1997
DOI: 10.3109/08941939709032155
|View full text |Cite
|
Sign up to set email alerts
|

Renal Artery Occlusion Model in Dogs for the Evaluation of Thrombolytic Agents

Abstract: The purpose of this study was to develop a model of renal artery occlusion and to investigate the effects of various thrombolytic agents on an acute occlusion of the renal artery with respect to ischemic tolerance of renal parenchyma. In order to do this, a thrombosis model in dogs (n = 36) was established and a total of 72 dorsal renal arteries occluded using autologous clot material. For the in vitro preparing of a clot, autologous blood (20 mL) was withdrawn and 100 U thrombin immediately added. Then 1 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…171 Urokinase was not associated with serious hemorrhage in that study. Urokinase has been used experimentally in dogs [172][173][174] and has been reported in 1 dog with PTE. 175 t-PA directly converts plasminogen to plasmin.…”
Section: Thrombolysismentioning
confidence: 99%
“…171 Urokinase was not associated with serious hemorrhage in that study. Urokinase has been used experimentally in dogs [172][173][174] and has been reported in 1 dog with PTE. 175 t-PA directly converts plasminogen to plasmin.…”
Section: Thrombolysismentioning
confidence: 99%
“…Ten studies supported the PICO question (all LOE 3, 3 good quality, 56,75,99 6 fair, 16,17,32,53,74,77 Of the 10 supporting studies, 4 demonstrated that a thirdgeneration thrombolytic agent was superior to a second-generation thrombolytic. Specifically, 2 studies supported that monteplase was superior to rt-PA, 53,56 1 noted that intraarterial reteplase was superior to IV alteplase, 35 and 1 that noted that IV reteplase was supe-rior to IV alteplase.…”
Section: Evidence Summarymentioning
confidence: 97%
“…11,12 Thirteen LOE 3 studies of fair quality supported the PICO question. [13][14][15][16][17][18][19][20][21][22][23][24][25] These studies included no thrombolytic control groups without randomization of group allocation. Zhang and colleagues injected a fibrin-rich embolus into the left anterior descending (LAD) coronary artery causing occlusion.…”
Section: Evidence Summarymentioning
confidence: 99%
See 2 more Smart Citations